2019
DOI: 10.1139/cgj-2018-0323
|View full text |Cite
|
Sign up to set email alerts
|

Hydromechanical behaviour of overconsolidated unsaturated soil in undrained conditions

Abstract: Hydromechanical behaviour of an unsaturated silt with various suctions and different overconsolidated ratios (OCRs) was investigated through a series of undrained triaxial tests (constant water contents, CW). All the samples were prepared from the slurry state. Different OCRs (= 1, 2, 4, and 8 in net stress) were achieved by unloading the samples to 400, 200, 100, and 50 kPa from an initial confining net pressure of 400 kPa. Then the samples were dried to various suctions (0, 100, 200, 300, and 400 kPa). Unsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…While the overconsolidation ratio (OCR) is often used in constitutive modeling of saturated soils, the dual effects of suction on the effective stress and yield stress imply that it is difficult to use this parameter in the interpretation of data. Nonetheless, Wu et al (2019) found that the shear strength of unsaturated sedimented soils depends on the OCR prior to desaturation.…”
Section: Volume Change Of Unsaturated Soilsmentioning
confidence: 99%
“…While the overconsolidation ratio (OCR) is often used in constitutive modeling of saturated soils, the dual effects of suction on the effective stress and yield stress imply that it is difficult to use this parameter in the interpretation of data. Nonetheless, Wu et al (2019) found that the shear strength of unsaturated sedimented soils depends on the OCR prior to desaturation.…”
Section: Volume Change Of Unsaturated Soilsmentioning
confidence: 99%
“…However, as stated by Hashiguchi 13 15 , classic elastoplastic constitutive models with a single yield surface enclosing the elastic domain possess many limitations in describing the mechanical response of soils. First, the original CASM predicts pure elastic behaviour inside the yield surface while the experimental data show that recoverable deformation only occurs within a very small range 16 19 . CASM describes discontinuous variation of the tangent stiffness modulus from elastic to plastic of over-consolidated soils and predicts an unsmooth stress–strain relation, and thus is unable to describe softening behaviour accurately 9 , 17 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…For the laboratory testing, large amounts of triaxial tests under different confining pressures, over-consolidated ratios (OCR) and axial strain rates were carried out to analyze the rate-dependent behavior of saturated clays at different initial states. [3][4][5][6] Besides, constant strain tests (CRS) were performed on reconstituted and natural clays in oedometer, allowing a unique relationship among stress, strain and strain rate to be identified. 7,8 The yield stress and shear strength were found to increase with increasing strain rate.…”
Section: Introductionmentioning
confidence: 99%